Design architecture of interoperability between electric vehicle charging operators and regulators - Prasetyo Aji; Riza Riza; Dionysius Aldion Renata; Tisha Aditya Anggraini Jamaluddin; Panca Kurniawan; Dhea Amelia Rianjani; Edward Edward (Institute of Advanced Engineering and Science, 2026)
The rapid expansion of electric vehicle (EV) charging infrastructure has resulted in a fragmented ecosystem characterized by multiple charging station (CS) operators and limited interoperability between operator platforms and regulatory authorities. This fragmentation creates challenges for service continuity, user experience, and evidence-based policy development. To address these issues, this paper proposes a regulatory-centric interoperability framework that enables standardized data exchange across heterogeneous CS management systems. The proposed solution employs a lightweight representational state transfer (REST) application programming interface (API)-based interoperability model in which the regulator assumes a dual role as both verifier and national data aggregator, allowing operators to share essential operational and transaction data without requiring proprietary protocol alignment. The framework demonstrates that secure and standards-compliant data harmonization can be achieved by leveraging existing backend charging data, thereby improving network visibility, regulatory oversight, and coordination among operators. By supporting structured reporting and cross-operator information exchange, the proposed approach enhances service reliability and facilitates informed infrastructure planning. This study contributes a scalable and policy-aligned interoperability foundation that supports the sustainable development of EV charging infrastructure and provides a basis for future extensions toward advanced grid integration and data-driven mobility governance.